(untitled) (Revista Paradigma, 2022)
Discussions regarding the inclusion of people with disabilities are necessary in view of the still existing exclusion scenarios. Although there is a vast international and national normative framework on the subject, accessibility, in all its spheres, remains a challenge for the effectiveness of the tutelage of these individuals. The ordinance to include permeates the obligations of society and the State, but the latter is responsible for doing it through public policies of the State. Given this premise, the research questions whether the Public Administration can use the argument of reserving the possible to refuse reasonable and necessary adaptations for the community experience of the person with disabilities. Through the deductive-critical method and using bibliographic research, it was concluded that the right to adapt is included in the concept of existential minimum, and it is not possible to stop doing so.